BUDIDAYA CACING AFRICAN NIGHT CRAWLER (EUDRILUS EUGENIAE) SEBAGAI PELUANG USAHA DI DESA TANJUNG, TULUNGAGUNG - Nina Lisanty; Wiwiek Andajani; Kharisma Satria Pamungkas; Taufan Achmad Ghozali Yusuf (Universitas Kadiri, 2025)
Tanjung Village, Tulungagung, has great potential in cultivating African Night Crawler earthworms (Eudrilus eugeniae), which are useful as animal feed and organic waste processors. However, the lack of community knowledge is the main obstacle in its development. This community service activity aims to provide education and training in earthworm cultivation through socialization, demonstrations, and direct practice, including media preparation, maintenance, and harvesting. Evaluations are carried out to measure the increase in participants' understanding and skills. The results of the activity showed a significant increase in cultivation skills, with several participants starting to apply the techniques they learned independently. In addition, community interest in this business has increased, opening up new economic opportunities. In conclusion, this training has succeeded in increasing community capacity in cultivating Eudrilus eugeniae and is expected to contribute to economic independence and sustainable use of local resources.